Improving Spiritual Quotient (SQ) in PAI Curriculum Development at MAN 2 Pamekasan - Mabnunah, Mabnunah; Kahfi, Shohibul; Nafilah, Anis Khofifatun; Jannah, Wakilatul (Jurnal Pendidikan Madrasah, 2023)
This study aims to determine the improvement of Spiritual Quotient (SQ) in the development of the Islamic Religious Education (PAI) curriculum at MAN 2 Pamekasan. This research uses qualitative methods. Data was collected through interviews, observation, and documentation. This study describes that the development of the PAI curriculum has basic principles, namely a holistic approach, an experiential approach, and ethical values that are applied in every aspect of life. The aspects developed in the curriculum include the development of knowledge and faith, morals and ethics, and the integration of SQ and EQ. These aspects are developed through main strategies that include the integration of religious subjects with social sciences, the development of extracurricular activities with religious themes, and the study of religious moderation. This approach aims to help students understand religion deeply and practice it in daily life, as well as help students develop their spiritual potential optimally.